Impoliteness Strategies in The Comedy Drama Karo Cot-Dogol - Sembiring, Rony Arahta; Arsen Nahum Pasaribu; Sondang Manik; Ester Alischa M (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Culture is the identity of a nation that must be maintained from generation to generation. The comedy drama Cot-Dogol shown in the Cot Dogol You Tube Channel account and how these illustrations influence behavior and social development in this ethnic group. The aims of this study is to examine the language impoliteness strategy in the Karo comedy drama Cot-Dogol and how it influences behavior and social development in the Karo ethnic group. In the comedy drama Karo Cot Dogol, one of the techniques used is to make the audience laugh in an impolite or inappropriate way. Typically, this strategy involves the use of crude humor, provocative jokes, or actions that disrupt social norms. The data for this research are transcripts of conversations taken from videos on the YouTube channel. The expected output is that the author can collect information about how to use this incivility strategy in arts and culture and social developments that occur amidst this ethnic group. This research uses a qualitative descriptive method where, in the data analysis process, researchers organize, group, sort, categorize, and find patterns and relationships that exist in the data. Based on the results of the analysis, it was found that there were 6 times of Bald on record, 8 times of positive impoliteness, 12 times of Negative impoliteness, 12 times of Mock impoliteness, 0 times of Withhold impoliteness. The drama intensively utilizes the strategy of impoliteness to generate laughter and humor. Where the type of negative and mock impoliteness has the highest intensity in the drama. The use of indirect language, subtle innuendo, and crude jokes are characteristic of the characters' dialogues